Mujeres, política y periodismo en la Argentina de los años cincuenta. La resistencia peronista a través de los periódicos Línea Dura y Soberanía - Gorza, Anabella (2016)
This article tries to make visible the politic activity developed by women in the Peronism Resistance through the analysis of two journals which confirmed the opposition press of those times: Línea Dura and Soberanía, directed by María Granata and Nora Lagos, respectively. The comparative analysis let us reach some conclusions about woman’s image and its relationship with politic buit from their own media. While in Línea Dura, where most articles were written by its director, we could see a contradiction between a traditional discourse that relates women politic activity to domestic scope, but on the other land shows them in different spaces of struggle, in Soberanía we see an absent director because of prision and exile, but who for this same reason got visibility and built on herself an image of a strong, fighting and self sufficient woman.